If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = (56 + -1x) + -321 Remove parenthesis around (56 + -1x) 3 = 56 + -1x + -321 Reorder the terms: 3 = 56 + -321 + -1x Combine like terms: 56 + -321 = -265 3 = -265 + -1x Solving 3 = -265 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 3 + x = -265 + -1x + x Combine like terms: -1x + x = 0 3 + x = -265 + 0 3 + x = -265 Add '-3' to each side of the equation. 3 + -3 + x = -265 + -3 Combine like terms: 3 + -3 = 0 0 + x = -265 + -3 x = -265 + -3 Combine like terms: -265 + -3 = -268 x = -268 Simplifying x = -268
| C^7*c^18/c^3*c^10=0 | | C^7*c^18/c^3*c^10 | | C-6(x+5)=15 | | 9a+-5-5a+8=0 | | (b+2)(b+2)=2.8284 | | A^7b^8=0 | | 200.00+0.5x=75.00+0.10x | | .25x+.50(73-x)=23.50 | | 5x-1=14-109 | | (2x^5y^2)(5xy^3z^2)(2yz)=o | | 0.25=1.5-5x | | .10x+.12y=900 | | x/53=90 | | 44=t | | x+58=-x+4 | | 3b^2-8=10b | | 3=1/5x=-5 | | 12X+8X=12X+5X+3 | | 7e-4=3 | | 13+.5=-3 | | r/15-16=16 | | 3x^2-12x+16= | | -4x^2+9y^2-24x-72=0 | | .66x+.75=.60(x-.625) | | 13+.57y=-3 | | 13=7x+6x | | (-3b/a^4)^2 | | 4x-6=9x+3 | | 7/4x=14 | | 2cos^2-1-cosx=0 | | 3x-x+8-4-5x-2=10 | | 3c*7e= |